A controlled cohort study of sickness absence and disability pension in colorectal cancer survivors. (June 2014) - Hauglann, Beate K.; Šaltytė Benth, Jūratė; Fosså, Sophie D.; Tveit, Kjell M.; Dahl, Alv A.
Abstract: Purpose. To investigate long-term development of sickness absence and disability pension among colorectal cancer (CRC) survivors compared to matched cancer-free controls, and to assess to what degree socio-demographic and disease characteristics influence these outcomes. Patients and methods. In a register-based cohort study with data from the Cancer Registry of Norway and longitudinal data from other national registries, 740 patients with CRC diagnosed 1992–1996 at the age 45–54 years were observed up to 14 years post-diagnosis. Also 740 matched controls were observed over the same time period. Results. During the first year after diagnosis, 85% of the CRC survivors were on sick-leave at some point, compared to 19% of the controls. Among survivors with localized cancer, 21% were on sick-leave 12 months after diagnosis, versus 33% with regional, and 52% with distant cancer. Survivors with rectum cancer were more likely than colon cancer survivors to be on sick-leave the first year after diagnosis (OR 2.53, 95% CI 1.61–3.98). CRC survivors were at higher risk for disability pension (DP) than controls, depending on extent of disease. Hazard ratios for DP were 1.67 (95% CI 1.13–2.46) for survivors with localized cancer, 3.12 (95% CI 2.06–4.72) for regional, and 10.13 (95% CI 4.17–24.62) for distant cancer, respectively. In survivors, distant cancer, low level of education, not having children < 18 years in the household, pre-diagnostic sick-leave and not being employed at diagnosis were associated with increased likelihood for DP. Conclusion. A considerable proportion of CRC survivors, for years after diagnosis, will experience reduced work ability compared to controls. Rehabilitation and workplace adjustment to reduce sickness absence and improve work ability should be a long-term concern.